Omsorgspersonalens kunskap om Salutogent förhållningssätt : En kvalitativ studie genomförd i Piteå kommuns äldreomsorg - Mikaelsson, Hanna (2014)
The last few years have elderly care in Sweden been extensively debated. Above all, the debate has been about eldercare design and staffing. Working in elderly care is about working with the very oldest people in our society. For many of these seniors have the pathogenic care come to its end , which means that many individuals are living with one or more diseases that can´t be cured. These oldest belong to the fastest growing segment of the population. Aaron Antonovsky (2005) came to ask the question "How is it that some people are able to maintain health despite being subjected to severe stress?" The question is about the origins of health. What characterizes the people who are able to maintain health? These people have something in common. Antonovsky came to call it common to the sense of coherence (SOC).The purpose of this thesis is that with a hermeneutic method to increase the understanding of care staff's knowledge of the salutogenic approach. Empirical research shows that care staff had received some knowledge of the subject but to the relatively small scale works from the salutogenic approach. The reason for this is according to respondents an unacceptably low staffing. Also described is that there are some difficulties in translating theory into practice by the respondents. Broady (1998) writes that Bourdieu's cultural capital among other means knowledge and to transform that knowledge into practice. But the basis of this, the cultural capital strengthened to contribute to and develop informants' knowledge of the salutogenic approach.Keywords: salutogenic, elder care, comprehensibility, manageability and meaningfulness. Validerat; 20140615 (global_studentproject_submitter)